2002
DOI: 10.1190/1.1500385
|View full text |Cite
|
Sign up to set email alerts
|

Seismic trace interpolation in the f‐x‐y domain

Abstract: Seismic trace interpolation is implemented as a 2-D (x, y) spatial prediction, performed separately on each frequency ( f ) slice. This so-called f-x-y domain trace interpolation method is based on the relation that the linear prediction (LP) operator estimated at a given frequency may be used to predict data at a higher frequency but a smaller trace spacing. The relationship originally given for the f-x domain trace interpolation is successfully extended to the f-x-y domain. The extension is achieved by maski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 10 publications
0
38
0
Order By: Relevance
“…The inner eye-wall appears relatively independent from the outer eye-wall with a diameter of 50 km at t = 14 h. It should be noted there are cyclonic vortices located on the outer eye-wall PV ring. A previous study (Wang 2002) also indicates mesoscale vortexes may exist near the eye-wall of hurricanes.…”
Section: (B) Formation Of Spiral Rain Bands Between Concentric Eye-wamentioning
confidence: 99%
See 1 more Smart Citation
“…The inner eye-wall appears relatively independent from the outer eye-wall with a diameter of 50 km at t = 14 h. It should be noted there are cyclonic vortices located on the outer eye-wall PV ring. A previous study (Wang 2002) also indicates mesoscale vortexes may exist near the eye-wall of hurricanes.…”
Section: (B) Formation Of Spiral Rain Bands Between Concentric Eye-wamentioning
confidence: 99%
“…Could a mesoscale model reproduce the large outer eye-wall, inner eye-wall and spiral rain band between them? Spiral rain bands near hurricane eye-walls have been recently explained by vortex Rossby wave theory (Guinn and Schubert 1993;Möller andMontgomery 1999, 2000;Wang 2002). After MacDonald (1968) hypothesized that the spiral rain bands in hurricanes are associated with Rossby-type waves, vortex Rossby waves in hurricanes have been studied using both observational data (Reasor et al 2000) and simplified numerical models (Melander et al 1987;Carr and Williams 1989;Sutyrin 1989;Shapiro and Montgomery 1993;Smith and Montgomery 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the function ) , ( x d ω is strictly sinusoidal and predictable in the x direction. Consequently, the trace can be predicted by the preceding or following traces with a spatial prediction filter (Spitz 1991, Wang 1999, 2002. .11) shows that the prediction filter in the x − direction is the complex conjugate of the filter in the x + direction.…”
Section: Appendix: Fx Prediction Filteringmentioning
confidence: 99%
“…In order to merge it with a neighboring modern 3D seismic dataset, I attempt first to regularize traces spatially and then to produce a refined output using a f -x-y domain trace interpolation method that is suitable for a spatially aliased data set (Wang, 2002). For this very specific data set, trace regularization is actually accomplished in two steps.…”
Section: Real Data Examplementioning
confidence: 99%
“…For instance, in seismic tomography, one commonly defines the cost function using the L 2 norm (the Euclidean norm) in the data space, incorporating the L 2 norm in the model space. In addition, one uses the L 2 norm of the model derivatives, attempting to penalize large spatial derivatives and to produce a smoothed model (Tarantola, 1987;Wang, 2003). The objective of this paper, however, is precisely opposite, that is, to find a sparse model with minimum structure.…”
Section: Introductionmentioning
confidence: 99%